Effects of Alkali Concentration and Conching Temperature on Flavour, Hardness and Colour of Chocolate - Misnawi Jati; Susijahadi .; Jinap Selamat; Teguh Wahyudi; Novrita Putriani (Indonesian Coffee and Cocoa Research Institute, 2006)
Alkalization is an addition of alkali into cocoa mass to improve product quality in terms of flavour and colour appearance. Sodium bicarbonate and potassium bicarbonate are usual to be added into cocoa cotyledon prior to roasting. A study has been carried out to evaluate the effects of alkalization proceeded upon conching on chocolate sensory properties, hardness and colour. Re sponse Surface Methodology design at alkali concentrations of 1—15 g kg -1 and conching temperature of 40—80 oC have been used in the study. Parameters evaluated were sensory properties, particle size, hardness and colour. Results of the study showed that alkali concentration significantly influenced aroma, overall preference, particle size and hardness; meanwhile, conching temperature showed significant influence on aroma, taste, appearance, overall preference and texture of chocolate. Alkali concentration and conching temperature showed interactively influence on aroma and overall preference. A good quality of chocolate could be found at the alkali concentration of 8—15 g kg -1 and conching temperature of 74—80 oC. Key words: cocoa bean, chocolate, flavour, conching, alkalization, colour, particle size, texture.